Successful treatment of non‐convulsive status epilepticus diagnosed using bedside monitoring by a combination of amplitude‐integrated and two‐channel simplified electroencephalography. Issue 2 (27th August 2015) - Egawa, Satoshi; Hifumi, Toru; Kawakita, Kenya; Manabe, Arisa; Matumura, Hikari; Okazaki, Tomoya; Hamaya, Hideyuki; Shinohara, Natuyo; Shishido, Hajime; Takano, Koshiro; Abe, Yuko; Hagiike, Masanobu; et al.
Abstract : Case: A 66‐year‐old man developed disturbed consciousness and right hemiparesis with transient convulsions in the right arm. Bedside monitoring using a combination of amplitude‐integrated electroencephalography and two‐channel simplified electroencephalography revealed intermittent episodes of 1–3 Hz δ waves lasting for approximately 5 min, consistent with non‐convulsive status epilepticus. Fosphenytoin (22.5 mg/kg/day) and levetiracetam (1, 000 mg) prevented right arm convulsions but did not restore consciousness. The two‐channel simplified electroencephalography also showed an intermittent periodic δ wave pattern in the Fp1‐C3 channel. Conventional electroencephalography revealed a polymorphic δ activity that was abolished by 2.5 mg diazepam, thus confirming the diagnosis of non‐convulsive status epilepticus. Outcome: The patient recovered completely with the antiepileptic drug combination. Conclusion: Immediate initiation of bedside monitoring using amplitude‐integrated electroencephalography and two‐channel simplified electroencephalography allows early detection of non‐convulsive status epilepticus in patients with disturbed consciousness, which considerably improves the prognosis.